Effect of Primed and Un-Primed Seeds on Germination, Growth Performance and Yield in Okra [Abelmoscus esculentus (L.) Moench] - Ankit Adhikari; Amit Shrestha (Turkish Journal of Agriculture: Food Science and Technology, 2020)
This research was conducted to overcome the problem of slow and erratic emergence in okra and to find out the effects of priming on germination, growth performance and yield in okra at Research Field of Nepal Polytechnic Institute (NPI) Bharatpur-11, Chitwan, Nepal (April-July, 2019). Arka Anamika variety was used for experiment. The experiment was laid out in Randomize Complete Block Design with 5 treatments and 4 replications, i.e. T1 (hormonal priming with IBA), T2 (hydro priming with fresh tap water), T3 (halo priming with NaCl), T4 (chemo priming with liquid urea) and T5 (un-primed seeds). Field experiment results showed that priming proved effective in improving germination percent except the chemo priming, reducing the mean germination time (MGT), improving the growth parameters (plant height, number of branches, plant canopy and number of leaves) and improving yield contributing characters like fruit length, fruit diameter as compared to un-primed seeds. The highest and lowest germination percentages were found in hydro priming and hormonal priming respectively while better growth performance in hormonal and chemo priming. Similarly, hormonal and hydro priming resulted in higher yield. Hence, it is suggested that seed priming is important to improve the overall germination, growth performance and yield in okra.